2015
DOI: 10.1111/ane.12474
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation in sensory neuropathy in prediabetes or diabetes

Abstract: To our knowledge, this is the first study to assess the relationships between TNF-α, IL-10, and NCS of the most distal sensory nerves in patients with prediabetes or type 2 DM. The mechanisms involved in the pathogenesis of DM and diabetic peripheral neuropathy are complex. The pro-inflammatory stage and the high incidence of neuropathy in patients with prediabetes may suggest a possible causative effect; however, the potential role of inflammation in the pathogenesis of peripheral neuropathy needs further cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
1
28
1
Order By: Relevance
“…The finding for IL-6 not only corroborates the report from the KORA F4 study (8) but also is in line with other cross-sectional studies investigating DSPN or impaired nerve conduction (5,17). By contrast, associations between higher TNF-a and DSPN or its components have so far been limited to small studies that did not adjust for confounding factors (6,7,9,15,31), whereas no associations were found in studies that considered confounders (5,8). From a mechanistic point of view, it is important to note that IL-6 and TNFa are functionally related: TNF-a activates the transcription factor nuclear factor-kB and thereby induces IL-6 expression.…”
Section: Il-6 Tnf-a and Incident Dspnsupporting
confidence: 88%
“…The finding for IL-6 not only corroborates the report from the KORA F4 study (8) but also is in line with other cross-sectional studies investigating DSPN or impaired nerve conduction (5,17). By contrast, associations between higher TNF-a and DSPN or its components have so far been limited to small studies that did not adjust for confounding factors (6,7,9,15,31), whereas no associations were found in studies that considered confounders (5,8). From a mechanistic point of view, it is important to note that IL-6 and TNFa are functionally related: TNF-a activates the transcription factor nuclear factor-kB and thereby induces IL-6 expression.…”
Section: Il-6 Tnf-a and Incident Dspnsupporting
confidence: 88%
“…Again, our result differs from the results of Duksal et al who found no correlations between TNF-α levels and conduction velocities in the studied nerves [47], but who assessed only dorsal sural and medial planter sensory nerves in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…These markers were further increased in those with painful DN [41], data that are in concert with findings from another study that reported increased IL-2 in participants with neuropathic pain [62]. Duksal et al recently reported that elevated serum levels of IL-6 and IL-10 in patients with prediabetes and T2DM correlated with markers of large nerve fiber sensory and motor axonal damage and with signs of motor nerve demyelination [63]. Since IL-10 is considered an anti-inflammatory cytokine, that negatively regulates TNF-α, one could speculate that the observed increased IL-10 levels in this study could have been a compensatory mechanism.…”
Section: Inflammation and Diabetic Neuropathymentioning
confidence: 58%